208 Association between cardiovascular data and the development and progression of mild cognitive impairment: results from the retrospective cohort study. (8th December 2021) - Faggiano, Andrea; Difonzo, Teresa; Avallone, Carlo; Forgione, Arianna; Gazzaniga, Valentina; Gramegna, Chiara; Locatelli, Giuseppe; Mallardi, Giulio; Nicotra, Alessia; Zago, Stefano; Carugo, Stefano
Abstract: Aims: Mild cognitive impairment (MCI) is characterized by objective evidence of cognitive impairment in one or more cognitive domains in the absence of significant interference in daily-life activities. Anyway, people with MCI are considered to be at heightened risk of further cognitive decline and progression to dementia. To date, few evidence regarding the association between cardiovascular data and MCI are present in the literature. To investigate the association between various cardiovascular data (traditional risk factors and outcomes) and the development and progression of MCI. Methods and results: The study included 127 patients referred to the Neurological Unit of the Fondazione IRCCS Ca' Granda Ospedale Maggiore Policlinico of Milan for subjective memory complaints and/or clinical suspect of cognitive impairment. Neuropsychological tests evaluating executive functions and cardiovascular data were collected at baseline and 2-year follow-up. Visit reports and medical records were reviewed to extrapolate the data. The study was conducted between 2012 and 2020. The 51 (40.2%) patients on antiplatelet therapy (94% on aspirin) had a worse baseline degree of cognitive impairment on neuropsychological tests of executive functions and had greater worsening of MCI at 2 years (Table 1 ). Patients on antiplatelet therapy were significantly older (75.85 vs. 71.7; P = 0.009), more ischaemic (21.6% vs. 1.3%; P < 0.001), hypertensive (90.2% vs. 60.5%; P < 0.001), and dyslipidaemic (62.7% vs. 19.7%; P < 0.001) than patients without antiplatelet therapy. No other single cardiovascular data analysed (presence of hypertension, dyslipidaemia, ischaemic heart disease, diabetes, atrial fibrillation, and anticoagulation therapy) showed a statistical significant association with MCI presence or progression. Conclusions: The present study suggests that the prevalence and progression of MCI is significantly higher among patients on antiplatelet therapy, who carry a greater cardiovascular burden. Although patients on antiplatelet therapy were older, more ischaemic, hypertensive, and dyslipidaemic than patients without antiplatelet therapy, none of these parameters were associated with MCI presence and/or progression and can therefore be considered a confounding factor.